A Case of S-Variant Hepatitis B Virus: An Immune System Escape Artist. (September 2021) - Shah, Amar S.; Civelli, Valerie F.; Bali, Varun; Johnson, Royce H.; Heidari, Arash
Genomic variants of the hepatitis B virus (HBV) preS/S protein are well-known to occur. Typically, immunity is gained through recovered HBV infection or by immunization. Very rarely, there are certain mutations that may enable HBV escape from the immune detection. PreS/S mutants may present with unpredictable pathobiologic, clinical, and transmittable implications. Standard laboratory testing for genomic HBV variants is not routinely performed by reference guidelines. s-variant HBV management remains challenging. Herein is a case of s-variant chronic HBV infection in a 55-year-old man. Diagnosis and treatment are described.